UPAYA DINAS KOPERASI, USAHA MIKRO, DAN PERDAGANGAN (DISKUMDAG) KOTA BATU DALAM MEMBERDAYAKAN PELAKU USAHA KECIL MENENGAH (UKM) PRODUK TUJUAN EKSPORT - Ruth Agnesia Sembiring; Tia Subekti; Mitha Mawar Nia Bella (Journal of Governance Innovation, 2020)
Abstract Small and Medium Enterprises are an important pillar in supporting the economy of the middle to lower class communities. Every region in Indonesia has SMEs but only a few are able to have export quality. Local products that are presented in the form of SMEs are often unable to compete with products from large-scale industries or even unable to compete with imported products. This is a threat to the economic continuity of the middle to lower class communities considering that today's global market opportunities are difficult to stem the flow of imports from other countries. One of the efforts that can be used to maintain SMEs is to improve the quality of SMEs with export standards. Batu City has 365 UKMs spread over 3 districts. This condition shows how UKM has become the economic support for the people of Batu. This research looks at "How are the efforts of the Office of Cooperatives, Micro Enterprises and Trade (Diskumdag) of Batu City in Empowering Small and Medium Enterprises (UKM) for Export Destination Products?" This research uses an interview, observation, and documentation methods. The theory used in this research is development theory with self-help and technocratic approaches and also the concept of community empowerment. As a result, first, the Batu City Government carried out the development of SMEs with a technocratic approach through the KITE IKM (Ease of Imports for Small and Medium Industry Export Destination) program. The technocratic approach is vertical and positions the government as a consultant. Second, the government provides training, mentoring, and facilities. However, out of a total of 365 SMEs, can export. Third, the main obstacle faced is that export quality standards have not been met.